Technique and Translation Quality of Directive Speech Acts in the Translation Product of Kitab Bulūghul Marām - Syifa Al Hasanah; Muhammad Yunus Anis (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2022)
This study aims to describe the types of directive illocutionary speech acts, translation techniques, and translation quality of directive speech acts in the translation of Kitab Bulūghul Marām. The research method used in this study is a descriptive qualitative method with data collection techniques, such as recording documents, questionnaires, and interviews. After that, the data were analyzed using the Spradley method in domain analysis, taxonomy, componential, and cultural themes. The study results show that from sixty-five data, there are six types of directive speech acts. Furthermore, in the translation technique, fourteen techniques are found 148 times. These techniques are found in three variants: couplet (75,9%), triplet (21,5%), and quartet (3,1%). Of sixty-five data, sixty-two data are translated accurately and acceptably, and three data are translated less accurately and less acceptably. On the other hand, sixty-three data (96,9%) have a high readability level, and two data have a medium readability level. From the assessment results of the three respondents in questionnaires, it is concluded that the translation quality of directive speech acts in Kitab Bulūghul Marām is in good category, with the average score of 2.91.